2021
DOI: 10.15376/biores.16.3.5390-5406
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and automated detection of surface knots on sawn timbers using YOLO-V5 model

Abstract: Knot detection is a challenging problem for the wood industry. Traditional methodologies depend heavily on the features selected manually and therefore were not always accurate due to the variety of knot appearances. This paper proposes an automated framework for addressing the aforementioned problem by using the state-of-the-art YOLO-v5 (the fifth version of You Only Look Once) detector. The features of surface knots were learned and extracted adaptively, and then the knot defects were identified accurately e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(53 citation statements)
references
References 39 publications
0
53
0
Order By: Relevance
“…The knottiness data used here were produced by the company Finnos using their in-house algorithms-we did not know their exact methods but rely on their credibility as trusted industrial supplier of the X-raying technology. In general, knot identification from Xrayed log tomographic images in the sawmilling industry is mostly based on convolutional neural networks locally trained for object detection (Fang, et al 2021). Ring properties were measured from the X-ray densitometric images, and due to the resolution of the images, the measurements of the small rings may contain relatively more error, than those of the larger rings.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…The knottiness data used here were produced by the company Finnos using their in-house algorithms-we did not know their exact methods but rely on their credibility as trusted industrial supplier of the X-raying technology. In general, knot identification from Xrayed log tomographic images in the sawmilling industry is mostly based on convolutional neural networks locally trained for object detection (Fang, et al 2021). Ring properties were measured from the X-ray densitometric images, and due to the resolution of the images, the measurements of the small rings may contain relatively more error, than those of the larger rings.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…Yolo has been updated to version five and is regarded as the state-of-the-art algorithm for object detection ( 24 ). It has been applied in many daily life aspects, such as the detection of surface knots ( 25 ) and real-time vehicles ( 26 ), as well as in various medical fields, including face mask recognition ( 27 ), breast tumor detection and classification ( 28 ), and chest abnormality detection ( 29 ). This study showed that the basic deep learning model Yolo V5 could handle the cyst-detection task, attaining F1, precision, and mAP scores of 0.832, 0.843, and 0.821, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…YOLO outperforms the other traditional object detection algorithms by examining (1) the images only once to find the objects inside them. Among all previous versions, YOLO V5 has a faster processing speed with the most advanced structure using parallel calculations [42,43]. Many new techniques are used in YOLO V5, such backbone (CSP-Darknet), neck (PAnet), head (YOLO layer) [44].…”
Section: You Only Look Once (Yolo) V5mentioning
confidence: 99%